Mushroom Powder Ameliorates the Metabolic Syndromes by Maintaining Glucose and Lipid Homeostasis in High Sugar Diet-fed Mice (Journal of Science and Technology Research, 2023)
Diets high in added sugar both directly and indirectly promote the development of metabolic diseases such as diabetes and obesity. The objective of this study was to evaluate the effects of mushroom powder (MP) in preventing the development of metabolic disorders caused by a high sugar diet. Swiss albino male mice were fed with normal diet (ND) or high sugar diet (HSD) in supplementation with or without mushroom powder. The results showed that supplementation of MP in high sugar diet effectively reduced the food intake and body weight of mice. Moreover, MP sustained glucose tolerance in HSD-fed mice and a significantly lower glucose level was observed in the MP supplemented group than that of the HSD group. Furthermore, kidney and heart weight were almost similar among the groups. However, MP supplementation significantly reduced the liver weight in comparison to that of HSD control group. The wet weights of white adipose tissue and brown adipose tissue were also lower in the MP supplemented groups in comparison to that of HSD group. In addition, supplementation of MP in the high sugar diet significantly decreased the level of total cholesterol, triacylglycerides, and LDL content. In conclusion, these results suggest that mushroom powder was effective in preventing the development of diabetes and obesity induced by a high sugar diet. As mushroom powder is an abundant source of nutrients, therefore, this powder can be an important dietary supplement for treating metabolic disorders instigated by a high-sugar diet.J. of Sci. and Tech. Res. 4(1): 13-24, 2022